BOYOLALI MILK CENTRE DENGAN PENDEKATAN GREEN ARCHITECTURE - Riza Auliwati; Edi Pramono Singgih; Suparno Suparno (Universitas Sebelas Maret Surakarta, 2015)
Design of Boyolali Milk Centre are motivated by the low numbers of milk consumption, the relatively low price of milk from dairy farmers to collectors, the lack of public knowledge processing technology products, and waste treatment. The mission of this project is to develop a major potential Boyolali to attract people who are still low in the milk through educational tours, so as to raise the living standards of farmers to absorb the results of local milk, milk-based industry to develop products, and as one of the tourist facilities that concept green (green). Design objectives are: to design a building that can facilitate information, educational tours, and marketing of milk based on the concept of Green Architecture. Design issues are: how the concept of green architecture can be translated to the expression of design forms an attractive building, reflecting the dynamic character of the milk, and contextuality of the environment (eco-friendly). The method used is a method of designing the Green Architecture (Green Architecture). The results obtained in the form of the design of an educational tour of the building named Boyolali Milk Centre which has never existed, consisting of dairy information center, museum milk, green pilot model dairy farm, green farm, mini plant / milk-based agro-industry, marketing center in the form of resto and milk shop, as well as play and sports facilities. Keywords: Education Travel, Green Architecture, Information Center, Milk Centre.